S 47445 Produces Antidepressant- and Anxiolytic-Like Effects through Neurogenesis Dependent and Independent Mechanisms - Mendez-David, Indira; Guilloux, Jean-Philippe; Papp, Mariusz; Tritschler, Laurent; Mocaer, Elisabeth; Gardier, Alain M.; Bretin, Sylvie; David, Denis J. (Frontiers in Pharmacology, 2017)
Glutamatergic dysfunctions are observed in the pathophysiology of depression. The glutamatergic synapse as well as the AMPA receptor’s (AMPAR) activation may represent new potential targets for therapeutic intervention in the context of major depressive disorders. S 47445 is a novel AMPARs positive allosteric modulator (AMPA-PAM) possessing procognitive, neurotrophic properties and enhancing synaptic plasticity. Here, we investigated the antidepressant/anxiolytic-like effects of S 47445 in a mouse model of anxiety/depression based on chronic corticosterone administration (CORT) and in the Chronic Mild Stress (CMS) model in rats. Four doses of S 47445 (0.3 to 10mg/kg, oral route, 4 and 5 weeks, respectively) were assessed in both models. In mouse, behavioural effects were tested in various anxiety-and depression-related behaviors : the elevated plus maze (EPM), open field (OF), splash test (ST), forced swim test (FST), tail suspension test (TST), fur coat state and novelty suppressed feeding (NSF) as well as on hippocampal neurogenesis and dendritic arborization in comparison to chronic fluoxetine treatment (18 mg/kg, p.o.). In rats, behavioural effects of S 47445 were monitored using sucrose consumption and compared to those of imipramine or venlafaxine (10 mg/kg, i.p.) during the whole treatment period and after withdrawal of treatments. In a mouse model of genetic ablation of hippocampal neurogenesis (GFAP-Tk model), neurogenesis dependent/independent effects of chronic S 47445 treatment were tested, as well as BDNF hippocampal expression. S 47445 reversed CORT-induced depressive-like state by increasing grooming duration and reversing coat state’s deterioration. S 47445 also decreased the immobility duration in TST and FST. The highest doses (3 and 10mg/kg) seem the most effective for antidepressant-like activity in CORT mice. Furthermore, S 47445 significantly reversed the anxiety phenotype observed in OF (at 1mg/kg) and EPM (from 1mg/kg). In the CMS rat model, S 47445 (from 1mg/kg) demonstrated a rapid onset of effect on anhedonia compared to venlafaxine and imipramine. In the CORT model, S 47445 demonstrated significant neurogenic effects on proliferation, survival and maturation of hippocampal newborn neurons at doses inducing an antidepressant-like effect. It also corrected CORT-induced deficits of growth and arborization of dendrites. Finally, the antidepressant/anxiolytic-like activities of S 47445 required adult hippocampal neurogenesis